Desentralisasi Fiskal dan Pola Ketergantungan Daerah Kota Batu Jawa Timur - pertiwi, vidya imanuari (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
Indonesia started implementing fiscal decentralization with the economic reforms of 1998. The expected outcome of its implementation is to stimulate economic development and achieve equitable economic development for all of Indonesia’s regions. However, the little local revenue in each region and the strong reliance of the regions on financial affairs to the central government are two barriers to the implementation of autonomy, especially fiscal decentralization. The analysis of fiscal decentralization’s implementation in Batu City is covered in this article, along with strategies for boosting municipal revenue. Utilizing secondary data a qualitative form of data collection is used. According to the study presented in this article, own regional revenue has a key role in determining how financially dependent a region is. Second, although Batu City is one of the cities in East Java with a bright potential for economic growth, the area’s fiscal dependency level is considerable. In order to combat budgetary reliance, efforts might be made to increase advertising levies and tax revenue from the tourism industry.